Organisational culture, the media and the school. - Muzvidziwa, Irene; Muzvidziwa, Victor N. (Top Shelve Publishers, 2016)
This paper seeks to explore the link between organisational culture, school effectiveness and the role of the media as a learning tool and how the media impacts on learning processes. While the media is acknowledged as an agent of socialisation until recently its role as a tool that impacts on learning processes in schools has been under played and few papers have been devoted to explaining the link between the media, organisational culture and education. This paper seeks to bridge that gap. The paper is divided into four sections. The first section defines culture and organisational culture in relation to the school. The second section links organisational culture to school effectiveness. The third section examines the role of the media as a socialisation agent with specific reference to educational settings. In the fourth section a discussion of the relationship between the media and the school is made. The last section presents a discussion of the role of the Internet in terms of the future of education in Africa.